Physiological effects of using a high-protein, low-carbohydrate diet of pregnant and lactating female rats on the development of their offspring - A. A. Makarcheva; I. D. Romanova; E. M. Inyushkina; R. A. Zaynulin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In the modern world, the nature of human nutrition is becoming more relevant. This is due to the spread of diseases such as diabetes mellitus, cardiovascular diseases and metabolic disorders. The health of a person and his offspring comes to the fore. In this regard, high-protein, low-carbohydrate diets are becoming popular at the moment.The aim of the study was to identify the effect of a high-protein, low-carbohydrate diet of pregnant and lactating female rats on the development of their offspring.Object and methods. The experiment was carried out on the offspring of female rats. The female rats of the control group received normal nutrition, and for the experimental group a special high-protein, low-carbohydrate diet was compiled, which was maintained throughout pregnancy and in the first week after delivery. As a result of the study, it was revealed that a diet with an increased protein content has a beneficial effect on the development of baby rats in delayed terms: they have a more pronounced weight gain, increased research activity and are less prone to anxiety.